2016
DOI: 10.1364/ol.41.000650
|View full text |Cite
|
Sign up to set email alerts
|

Laser-frequency locking to a whispering-gallery-mode cavity by spatial interference of scattered light

Abstract: We present a simple and effective method for frequency locking a laser source to a free-space-coupled whispering-gallery-mode cavity. The scheme relies on the interference of spatial modes contained in the light scattered by the cavity, where low- and high-order modes are simultaneously excited. A dispersion-shaped signal proportional to the imaginary component of the resonant optical field is simply generated by spatial filtering of the scattered light. Locking of a diode laser to the equatorial modes of a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…However, no correlated change was observed in the photon lifetime. Next, we have frequency-locked the laser on one of the narrowest resonances using an all-optical feedback loop 13 and we have calculated the fast-Fourier transform (FFT) of the transmission and scattering signals. From the FFT noise spectra only an overall increase in the amplitude noise is found on resonance without any noticeable spectral feature associated with high-frequency vibrations or surface waves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no correlated change was observed in the photon lifetime. Next, we have frequency-locked the laser on one of the narrowest resonances using an all-optical feedback loop 13 and we have calculated the fast-Fourier transform (FFT) of the transmission and scattering signals. From the FFT noise spectra only an overall increase in the amplitude noise is found on resonance without any noticeable spectral feature associated with high-frequency vibrations or surface waves.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, a servo amplifier is used as a feedback element to control the laser wavelength. A suitable frequency discriminator to drive the servo input can easily be obtained from the far-field spatial mode interference between scattered WGMs without resorting to conventional radio-frequency modulation schemes 13 . To observe the cavity ringing signals ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, it has also been shown that a suitable frequency discriminator for laser-to-microcavity locking can be derived from the interference of multiple cavity modes or, in the free-space excited droplets, from the scattered WGMs [41]. Thus, the light reflected by the cavity contains the interference pattern among wavefronts of various modes (see inset of Figure 3).…”
Section: Droplets As Optical Microcavitiesmentioning
confidence: 99%
“…By spatial selection of the cavity scattered light, the interference term between a narrow WGM and a secondary mode is recovered, the latter acting as a phase reference. This selection can be carried out by a diaphragm, located just in front of the photodetector PD2, whose position must be carefully adjusted until an odd-symmetrical profile is obtained [41]. The resulting signal exhibits a dispersive lineshape with a symmetry point located at the main resonance center and an amplitude proportional to the imaginary component of the resonant optical field.…”
Section: Droplets As Optical Microcavitiesmentioning
confidence: 99%